TRUST AND NETWORKS IN CLIMATE CHANGE ADAPTATION STRETEGIES: EXPERIENCE OF ACEH AND YOGYAKARTA IN EARTHQUAKE INTERVENTION - Muhammad Ulil Absor (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2018)
AbstractIndonesia is one of the most disaster-prone countries where 1,782 disasters occurred between 2002 and 2007. The devastating impacts of the disasters, particularly the earthquake in Aceh and Yogyakarta, attracted public participation from various institutions.  The high participation of the institutions to some extent caused program ineffectiveness as many of those institutions have overlapping roles and fight over funding and beneficiaries. This paper will critically examine why networking is important in climate change adaptation based on the lessons learnt of disaster response in Aceh and Yogyakarta earthquake. This paper argues that the participation of stakeholders needs an effective networking. Networks are certainly becoming necessary in disaster intervention to avoid overlapping roles and conflict of interest between institutions involved in disaster response. Networks in community levels also become social capital that increases community’s resilience upon disaster. Keywords: disaster, intervention, social capital